Perancangan Sistem Stokopname Berbasis Web pada Toko Bangunan Mutiara - Syech Syech; Maulana Sandy; Wasis Haryono (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
We designed and implemented a web-based inventory system to address challenges in managing inventory and financial data at Toko bangunan Mutiara. With high daily transaction volumes and a wide variety of products, manual recording often leads to errors, inaccuracies in inventory data, and difficulties in monitoring cash flow. To address this, we developed the system using the Agile/Scrum development model, which allows for flexibility and adaptation to user needs through the stages of Requirements, Design, Development, Testing, Deployment, and Review. The system was developed using web technology, including PHP and JavaScript for the backend, HTML and CSS for the frontend, and MySQL as the database system. The main features we implemented include two integration options: barcodes and unique product codes to simplify recording, automatic notifications when stock reaches the minimum level set by the system, and the ability to generate accurate reports. It is hoped that this research, which was designed to enhance operational efficiency in recording incoming and outgoing goods, provide flexible and accurate access to inventory data, and minimize errors in recording and inaccurate data, will be successful. The implementation of this system contributes to more accurate inventory management and supports better financial decision-making for Toko bangunan Mutiara.